Terapi spiritual emotional freedom technique (SEFT) untuk penanganan gangguan neurotik - Hidayatullah, Rizki Maulana; Indana, Finanin Nur (PSYCOMEDIA : Jurnal Psikologi, 2024)
This study aims to examine the effectiveness of the Spiritual Emotional Freedom Technique (SEFT) in reducing neurotic levels among 10th-grade students at SMA Ibrahimy 2 Sukorejo, Pondok Pesantren Salafiyah Syafi’iyah Sukorejo. SEFT is a therapeutic method that integrates energy psychology with a spiritual approach to address emotional, physical, and mental disorders holistically. The research employed a pre-experimental one-group pretest-posttest design, utilizing total sampling of 126 students with very high neurotic levels. The Neuroticism Scale Questionnaire (NSQ) was used to measure changes in neurotic levels before and after the intervention. Paired sample t-test analysis revealed a significant reduction in neurotic levels after the therapy, with a t-value of 18.79 and p = 0.000. The average pretest score of 53.54 decreased to 43.29 in the posttest, indicating a significant difference. This study concludes that SEFT is effective in reducing neurotic levels among high school students and can be recommended as an intervention to support students' mental health, particularly in the context of Islamic boarding school education.